The “Dogs’ Catching Mice” conjecture in Chinese phonogram processing - Meng Jiang; Qi Luo; Xia Wang; Ya Tan (PLoS ONE, 2025)
In Chinese phonogram processing studies, it is not strange that phonetic radicals contribute phonologically to phonograms’ phonological recognition. The present study, however, based on previous findings of phonetic radicals’ proneness to semantic activation, as well as free-standing phonetic radicals’ possession of triadic interconnections of orthography, phonology, and semantics at the lexical level, proposed that phonetic radicals may contribute semantically to the host phonograms’ phonological recognition. We label this speculation as the “Dogs’ Catching Mice” Conjecture. To examine this conjecture, three experiments were conducted. Experiment 1 was designed to confirm whether phonetic radicals, when embedded in phonograms, can contribute semantically to their host phonograms’ phonological recognition. Experiment 2 was intended to show that the embedded phonetic radicals employed in Experiment 1 were truly semantically activated. Experiment 3, on top of the first two experiments, was devoted to demonstrating that the semantically activated phonetic radicals, when used as independent characters, can truly contribute semantically to their phonological recognition. Results from the three experiments combine to confirm the conjecture. The implication drawn is that phonetic radicals may have forged two paths in contributing to the host phonograms’ phonological recognition: one is the regular “Cats’ Catching Mice” Path, the other is the novel “Dogs’ Catching Mice” Path.